The Effect of the Use of Jackfruit Juice (Artocarpus heterophyllus) in the Making of Cendol on Physical Properties and Sensory Quality - Syarifah, Dinda Lailatus; Sachriani, Sachriani; Ngurah S, I Gusti Ayu (Sahabat Publikasi, 2025)
This research aims to analyze the effect of using jackfruit juice (Artocarpus heterophyllus) in the production of cendol on its physical characteristics and sensory quality. The background of the research stems from the high use of synthetic colorants in cendol, which may pose health risks. Jackfruit juice was chosen due to its content of natural carotenoid pigments that can serve both as a coloring agent and as a source of the fruit's distinctive aroma and flavor. The research was conducted at the Food Processing Laboratory and the Laboratory of Food Material Engineering and Analysis, Culinary Education Study Program, Faculty of Engineering, Jakarta State University. This experimental study employed a Completely Randomized Design (CRD) with three treatment levels of jackfruit juice concentration (50%, 60%, and 70%). Physical tests included measurements of color and chewiness, while sensory evaluation—covering color, aroma, taste, surface texture, and chewiness—was conducted using a hedonic test by semi-trained panelists. Statistical hypothesis testing using ANOVA showed that the addition of jackfruit juice had no significant effect on physical characteristics, with color values ranging from 30.78 to 33.00 and chewiness from 9.83 to 15.5. Sensory quality testing using the Kruskal-Wallis test revealed a significant effect on the color attribute, with further analysis using Tukey’s test indicating that the 70% concentration was most preferred. No significant differences were found in other sensory aspects. It can be concluded that jackfruit juice can serve as a natural coloring and flavoring agent that enhances the physical and sensory quality of cendol.